Perluasan Kewenangan dan Penegakan Hukum Praperadilan di Indonesia dan Belanda - Kripsiaji, Dinar; Minarno, Nur Basuki (Al-Mazaahib: Jurnal Perbandingan Hukum, 2022)
This article examines the expansion of pretrial authority based on the Constitutional Court Decision Number 21/PUU-XII/2014, which focuses on the philosophy of pretrial in the context of the protection of human rights and the comparison of pretrial enforcement in Indonesia and the Netherlands. This article is qualitative research by utilizing data sourced from the library (library research), this article uses several approaches, they are: legal approach, case approach, comparative approach and conceptual approach. The decision of the Constitutional Court Number 21/PUU-XII/2014 is expected to bring hope, but there are still many problems that have occurred and have caused criticism. This post-decision pretrial was made with a more concrete formulation in the Draft Criminal Procedure Code and prioritized the interests of the suspect. This control effort emphasizes the principle of balance in the protection of human rights for suspects. This article concludes that the Constitutional Court Decision Number: 21/PUU-XII/2014 is expected to provide optimism, although there are still many obstacles that arise. As a recommendation, the House of Representative is expected to be able to draw up regulations regarding the expansion of pretrial authority at the investigation stage. Based on this, an integrated criminal justice system is needed and pretrial is still used in the draft KUHAP with a more explicit formulation that prioritizes the interests of the suspect.